Improving accuracy for stereotactic body radiotherapy treatments of spinal metastases. (26th June 2018) - Rijken, James; Jordan, Barry; Crowe, Scott; Kairn, Tanya; Trapp, Jamie
Abstract: Purpose: Use of SBRT techniques is now a relatively common recourse for spinal metastases due to good local control rates and durable pain control. However, the technique has not yet reached maturity for gantry‐based systems, so work is still required in finding planning approaches that produce optimum conformity as well as delivery for the slew of treatment planning systems and treatment machines. Methods: A set of 32 SBRT spine treatment plans based on four vertebral sites, varying in modality and number of control points, were created in Pinnacle. These plans were assessed according to complexity metrics and planning objectives as well as undergoing treatment delivery QA on an Elekta VersaHD through ion chamber measurement, ArcCheck, film‐dose map comparison and MLC log‐file reconstruction via PerFraction. Results: All methods of QA demonstrated statistically significant agreement with each other ( r = 0.63, P < 0.001). Plan complexity and delivery accuracy were found to be independent of MUs ( r = 0.22, P > 0.05) but improved with the number of control points ( r = 0.46, P < 0.03); with use of 90 control points producing the most complex and least accurate plans. The fraction of small apertures used in treatment had no impact on plan quality or accuracy ( r = 0.29, P > 0.05) but rather more complexly modulated plans showed poorer results due to MLC leaf position inaccuracies. Plans utilizing 180 and 240 control points produced optimal plan coverage with similar complexity metrics to each other. However, plans with 240 control points demonstrated slightly better delivery accuracy, with fewer MLC leaf position discrepancies. Conclusion: In contrast to other studies, MU had no effect on delivery accuracy, with the most impactful parameter at the disposal of the planner being the number of control points utilized.